Complex of Lascoux in Partition (3,3,2) - R. Hassan, Haytham; Aziz, Alaa Omer (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper, the complex of Lascoux in the case of partition (3,3,2) has been studied by using diagrams ,divided power of the place polarization ) (k ijï‚¶ ,Capelli identites and the idea of mapping Cone .